Developing a Digital Library Framework for Archiving Maritime Engineering Blueprints - Jeyachandran, S.; Kumar, Shathish (Indian Journal of Information Sources and Services, 2025)
The organizational structures of Maritime Engineering blueprints serve as vital documents in the ship's life cycle, from its design, construction, building, maintenance, and legal compliance. These documents are stored in legacy physical or antiquated digital systems, which are prone to degradation, loss, and retrieval inefficiencies. This work proposes a digital archive dedicated to the long-term preservation and safeguarded access of maritime engineering blueprints. The proposed framework strives to solve crucial problems like large format files (CAD and BIM models), metadata uniformity, effective management, long-term preservation, and retrieval. This investigation starts with a review of existing systems based on metadata standards for digital archiving engineering documentation. Subsequently, the design of the modular framework is based on a metadata schema that incorporates Dublin Core and MARC21 with maritime domain-specific extensions. The architecture uses open-source system components to provide horizontal storage scalability, indexed searchability, and role-based access control. A prototype system was developed based on Space with customizations to support blueprint digitization workflows, such as high-speed multi-page document scanning, optical character recognition (OCR), and format conversions. Evaluation of the system demonstrates improved blueprint retrieval times, precision of maritime metadata, and overall satisfaction among users. The framework has promising features for incorporating other emerging technologies, such as blockchain for versioning and Artificial Intelligence for auto-classification of engineering documents.